2019
DOI: 10.3390/admsci9030072
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Monetary Incentives on Individual and Organizational Performance in an Italian Public Institution

Abstract: This paper addresses the role of monetary incentives with regard to the performance of employees and organizations. The distribution of monetary incentives among employees in public administration has been investigated. Specifically, the traditional approach of bureaucracy that pays a premium to each employee, based on the position held, is compared with a merit approach which tends to recognize and reward individual contributions. A task advice centrality indicator and a value index have been defined and used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
1
12
0
2
Order By: Relevance
“…show that including the "life skills" variables defined in Cainarca et al (2019), the results discussed in Section 5 and 6 are confirmed.…”
Section: Appendix Asupporting
confidence: 57%
See 4 more Smart Citations
“…show that including the "life skills" variables defined in Cainarca et al (2019), the results discussed in Section 5 and 6 are confirmed.…”
Section: Appendix Asupporting
confidence: 57%
“…Finally, comparing the results of the investigation published in Cainarca et al (2019) with the ones obtained here, we also address the reverse causality issue because if the monetary incentives induce a virtuous employee behavior, it means that the monetary incentives are distributed according the employee performance, which means that the monetary incentives represent a bonus for the employee performance.…”
Section: Historical Incentive 2011mentioning
confidence: 85%
See 3 more Smart Citations